Der Begriff der Bildung in Deutschland. Zwischen Philosophie und Pädagogik - Sola, Giancarla; Dörpinghaus, Andreas; Witte, Egbert; Casale, Rita; Breithausen, Jutta (Studi sulla Formazione/Open Journal of Education, 2016)
The article ‒ in its five paragraphs, respectively signed by Giancarla Sola, Andreas Dörpinghaus, Egbert Witte, Rita Casale, Jutta Breithausen ‒ represents an endeavor to reconstruct the concept of “Bildung” in Germany. It does this primarily by moving from the meaning that this word has acquired both in the history of Bildung and in the German and “Mittel”-European history. At this glance toward the past, but also threw in the future, as well as in the present, follows an interconnection of relations between Bildung, Empirie and Erfahrung. This last concept places the idea of “experience” in connection with its hermeneutic comprehension. Therefore, the article also thematizes the dialectical legacy of Hegel and Humboldt in the context of the history of German Philosophy and Pedagogy. Then, the article considers the metamorphosis of Bildung after Nationalsozialismus ‒ from 1945 onwards ‒, analyzing the social-economic and political-legal context through the use of a "critics" capable of digging in the relationship between Bildung and Kultur. The article does that focusing, in its final part, on the concept of Widerstreit ‒ "resistance" –, related to a Skepsis understood also as a possible interpretative category of modernity. Thus, the article, in its overall unity, sizing its axial figure ‒ centered on the cultures of Bildung ‒ placing it on the intersecting planes represented by Philosophy and Pedagogy.